Interferences reduction in ECG signals applying IIR digital filters (2007)
Its shows the results of IIR digital filters application to the total or partial elimination of high frequency interferences, that affect the morphology of the Electrocardiogram signals (ECG). Also it describes a method for the IIR filters design  in discrete time, from its dynamics in continuous time. Additionally a method that relates the cut frequencies with the sampling frequencies is proposed. Some basic recommendations and specifications are presented to carry out the filters design that complies with the standards required for this type of signals.